1988
DOI: 10.1115/1.3250610
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments in Contact Conductance Heat Transfer

Abstract: The characteristics of thermal contact conductance are increasingly important in a wide range of technologies. As a consequence, the number of experimental and theoretical investigations of contact conductance has increased. This paper reviews and categorizes recent developments in contact conductance heat transfer. Among the topics included are the theoretical/analytical/numerical studies of contact conductance for conforming surfaces and other surface geometries; the thermal conductance in such technological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
0
3

Year Published

1998
1998
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(64 citation statements)
references
References 0 publications
4
57
0
3
Order By: Relevance
“…Many studies have been reported concerning thermal contact resistance and its reciprocal, the thermal contact conductance, an important issue in the optimum thermal design of such systems. However, as has been pointed out in many comprehensive reviews [2][3][4][5], there are still very wide discrepancies between experimental results from different investigators, even for similar materials.…”
Section: Introductionmentioning
confidence: 91%
“…Many studies have been reported concerning thermal contact resistance and its reciprocal, the thermal contact conductance, an important issue in the optimum thermal design of such systems. However, as has been pointed out in many comprehensive reviews [2][3][4][5], there are still very wide discrepancies between experimental results from different investigators, even for similar materials.…”
Section: Introductionmentioning
confidence: 91%
“…Les résistances thermiques de contact sont dues à un mauvais contact à l'échelle macrosco pique entre deux objets [Madhusudana et Fletcher, 1986] [Madhusudana, 1996] [Fletcher, 1988] [Bardon, 1972], À la séparation entre les deux objets, il va se former une couche de transition qui peut être faible si les milieux adhèrent parfaitement l'un à l'autre. Cette couche peut être plus importante s'il s'agit d'un contact entre deux milieux ayant des irré gularités de surface réunies par un liant (collage, soudure) ou simplement accolées avec un fluide interstitiel (air par exemple) comme le montre la figure 2.1.…”
Section: Contact Thermiqueunclassified
“…Since the regions of contact and gap are randomly distributed on any real surface, a parameter representing their effect, on the average, is required for engineering computations. The joint thermal contact conductance represents such a parameter, and has been widely studied 1,2 for metal-metal contacts. It should be noted that the term "contact conductance" is generally used in the literature for the joint thermal conductance; we follow the same usage for clarity, and the conductance at contacts is brought out specifically where applicable.…”
Section: Introductionmentioning
confidence: 99%